Retinal ischemia due to different stages of atherosclerosis - insights from a retrospective study on central retinal artery occlusion - Felix Schlachetzki; Ina Feistenauer; Michael Ertl; Mustafa Kilic; Fabian Aden; David Pollinger; Horst Helbig; Christina Wendl; Karin Pfister; Lars Krenkel; Maria Andreea Gamulescu; Ralf Andreas Linker; et al. (Neurological Research and Practice)
Abstract Background Ischemic stroke (IS) and retinal ischemia (IR) share similar vascular risk factors, but differ in their risk for subsequent or recurrent stroke and therapeutic options. This study characterizes the cardiovascular risk profiles and magnitude of atherosclerosis of the carotid artery of patients with central retinal artery occlusion (CRAO) in relation to the presence of the retrobulbar “spot sign” on orbital color-coded sonography (OCCS). Methods We performed a retrospective analysis on the detailed cardiovascular risk factors and neuroimaging data in patients with IR presenting between 2009 and 2023. Based on OCCS findings, CRAO were further divided into hyperechoic (“spot sign positive”, ssCRAO) or hypoechoic CRAO (heCRAO). Statistical analyses were performed with Mann-Whitney-U and χ [2] testing. P-values were considered significant if < 0.05. Results Overall, 112 patients were identified (heCRAO: n = 32; ssCRAO: n = 80). ssCRAO patients were significantly older (median 74 years vs. 66.5 years, Mann-Whitney-U: p-value < 0.001). Overall, 15/103 (14.6%) patients had concurrent acute ischemic stroke– 9 in the ipsilateral internal carotid territory, 2 in other territories and 4 disseminated. Further significant differences were found regarding the echogenicity of atherosclerosis (AS) in the two subgroups with (mainly) echorich AS being more common in the ssCRAO group (p-value < 0.001, n = 108) and the distribution of high-grade vs. low-grade stenoses of the ipsi- and contralateral carotid artery (p-value < 0.05, n = 99). 20 out of 112 patients had atrial fibrillation (aFib) with 17 of these being on ongoing oral anticoagulation. Conclusion According to this study, atherosclerosis may be one of the most important risk factors for IR while a specific embolic source could not be demonstrated (i.e. acute plaque rupture). By contrast, current oral anticoagulation for aFib in CRAO patients was high, thus only an incidental finding and may be an incidental finding due to its prevalence in the elderly. Furthermore, we were able to distinguish two subgroups of IR that differ in risk factors and most likely also in etiology, therapy and prognosis. The study underlines the importance of OCCS to detect “spot signs” in IR with indications for both, acute thrombolysis and secondary prevention.